Timing of Colostrum Expulsion Based on Type of Labor in Fourth Period Laboring Mothers - Sonya Lestari Aritonang; Lenny Irmawaty Sirait; Rupdi Lumban Siantar (Journal of World Future Medicine, Health and Nursing, 2023)
Colostrum is the best food and is an antibody for babies. Breast milk is a nutritional requirement for newborns, colostrum is yellow, low in fat but high in carbohydrates, protein and especially antibody content. This study aims to determine the relationship between the type of delivery and colostrum excretion in women in the fourth stage of labor. This type of research is a quantitative study using observational analytic methods. The population in this study were all mothers giving birth in the fourth stage at EMC Pulomas Hospital as many as 80 respondents. The statistical test uses the chi-square test. There is a significant relationship between the type of delivery and the time the colostrum comes out at the EMC Pulomas Hospital, Jakarta. evident from the value of p = 0.002. There is a significant relationship between the type of delivery and the time colostrum is released at EMC Pulomas Hospital, Jakarta, so it is necessary to provide counseling on types of delivery and its side effects